Nonlinear Rayleigh surface waves to characterize microscale damage due to alkali-silica reaction (ASR) in full-scale, nuclear concrete specimens. (20th October 2018) - Kim, Gun; Park, Sangyun; Kim, Jin-Yeon; Kurtis, Kimberly E.; Hayes, Nolan W.; Jacobs, Laurence J.
Abstract: Nonlinear Rayleigh surface waves are used to monitor the damage state due to alkali-silica reaction (ASR) in full-scale reinforced concrete block specimens created as part of a full-scale testing program for concrete nuclear containment structures. The measurement technique uses a wedge/transducer source to generate and a non-contact, air-coupled receiver to detect nonlinear Rayleigh surface waves to obtain the acoustic nonlinearity parameters for three different reinforced block concrete specimens – a confined and an unconfined ASR specimen, plus a control specimen – at three different time intervals. These results further validate the utility of nonlinear Rayleigh waves to quantify the progress of microscale damage due to ASR in full-scale, concrete structures.